Elongation of the disc-fovea distance and retinal vessel straightening in high myopia in a 10-year follow-up of the Beijing eye study - Rahul A. Jonas (Nature Portfolio, 2021)
Abstract To assess changes in the disc-fovea distance (DFD) in highly myopic eyes in a 10-year population-based follow-up study. The case control study included all highly myopic eyes (myopic refractive error ≥ − 6.0 diopters or axial length ≥ 26.0 mm) and a randomized group of non-highly myopic eyes examined in the population-based Beijing Eye Study 2001 and 2011. Using fundus photographs and optical coherence tomographic images, we assessed changes in DFD, parapapillary gamma zone, angle kappa (angle between the temporal arterial arcades), and course of papillo-macular retinal vessels. The study included 89 highly myopic eyes and 86 non-highly myopic eyes. DFD elongation, gamma zone widening, angle kappa decrease and straightening of papillo-macular retinal vessels were detected more often (all P < 0.001) in the highly myopic group than in the non-highly myopic group (63/89 versus 9/86;75/89 versus 18/86;61/89 versus 9/86; and 58/89 versus 7/86,respectively). Gamma zone enlargement, angle kappa reduction and papillo-macular retinal vessel straightening were significantly (all P < 0.001) associated with DFD elongation. The length of macular Bruch’s membrane on the disc-fovea line and the vertical distance between the temporal arterial arcade did not change during follow-up. DFD elongation (10-year incidence 70.8% in highly myopic eyes) was associated with gamma zone enlargement, while macular Bruch’s membrane length remained unchanged. It supports the notion of a temporal shift of an otherwise stable posterior Bruch’s membrane in axially elongated eyes. Straightening of the papillo-macular vessels with increasing gamma zone width suggests a coincident stretching of the papillo-macular retinal nerve fibers and inner limiting membrane.